Aural disturbance in the stories of M. R. James. Issue 1 (1st June 2021) - Hayes, Tracy
The physical process of receiving and interpreting sound creates not just an auditory experience through vibrations registering within our bodies; sounds can also evoke feeling and conjure up mental images. This is especially true of acousmatic sounds, which Michel Chion describes as sounds that are heard while their source remains invisible, and such sounds are thus perfect vehicles for conveying one feeling in particular: terror. If one is not able to see what one can hear, the ensuing sense of terror is heightened. Through the use of sound, and indeed the deliberate absence of sound, M. R. James, I would like to argue, is able to concoct in his stories an atmosphere of malevolence, in which his 'executors of unappeasable malice' (as Michael Cox describes them) are often heard rather than seen. This emphasis on sound over image, and the manipulation of it, can be traced back to the fact that James was an oral storyteller before he was a writer of fiction, and that his tales were originally intended for a listening audience. A linguist with an 'ear' for language and an aptitude for mimetic brilliance, James deploys alien soundscapes and aural disturbance to create sound as a tangible element within rich sonic tapestries that feature unique aural signatures and instances of acoustic chaos. Drawing on the work of David Hendy on 'the primalness of the auditory', Leigh Schmidt on 'sound corporeality', and Jonathan Sterne on 'acoustic culture', this article demonstrates how James utilized auscultation (or the act of listening) to promulgate terror through auditory images as elusive shape-shifters.